Health-related quality of life of patients of Brazilian primary health care - Ascef, Bruna de Oliveira; Haddad, João Paulo Amaral; Álvares, Juliana; Guerra Junior, Augusto Afonso; Costa, Ediná Alves; Acurcio, Francisco de Assis; Guibu, Ione Aquemi; Costa, Karen Sarmento; Karnikowski, Margô Gomes de Oliveira; Soeiro, Orlando Mario; Leite, Silvana Nair; Silveira, Micheline Rosa (Revista de Saúde Pública, 2017)
OBJECTIVE: To analyze the Health-Related Quality of Life (HRQoL) of patients of the primary health care of the Brazilian Unified Health System (SUS) and its associated factors. METHODS: This is a cross-sectional study with data from the Pesquisa Nacional sobre Acesso, Utilização e Promoção do Uso Racional de Medicamentos – Serviços, 2015 (PNAUM – National Survey on Access, Use and Promotion of Rational Use of Medicines – Services, 2015). Data were collected with a questionnaire that included the EuroQol 5 Dimensions (EQ-5D) instrument. Patients from the five regions of Brazil were interviewed. Multiple linear regression was used to analyze their Health-Related Quality of Life and its associated factors. RESULTS: Of the total of 8,590 patients, the most frequent dimensions were pain/discomfort (50.7%) and anxiety/depression (38.8%). About 10% of the patients reported extreme problems in these dimensions. The following factors were significantly associated with a worse quality of life: being female; having arthritis, osteoarthritis, or rheumatism; cerebrovascular accident; heart disease; depression; health self-assessment as poor or very poor; drinking alcoholic beverages once or more per month; dieting to lose weight, avoiding salt consumption, and reducing fat intake. Significant association was observed between a better quality of life and: living in the North and Southeast regions of Brazil; practicing physical activities; and having a higher educational level. No association was observed with factors related to the health services. CONCLUSIONS: The Health-Related Quality of Life of patients was influenced by demographic and socioeconomic factors that were related to health conditions and lifestyle, being useful to guide specific actions for promoting health and the integral care to patients of the Brazilian Unified Health System